Molecular docking evaluation of the insecticidal impacts of some essential oils’ constituents - Lebbal, Salim; Benhizia, Toufik; Rahal, Khalid; Zeraib, Azzeddine (ENTOMOLOGIA HELLENICA, 2026)
For a sustainable agriculture, the use of biopesticides is among the main components of Integrated Pest Management. When compared to chemical pesticides, biopesticides derived from plants offers numerous benefits. Additionally, the use of in silico approach could assist researchers in reducing the duration and expense of in vitro experiments. In this context, the current study’s objective is to predict the binding potential of Salvia microphylla (Lamiaceae) essential oils, in addition to two active ingredients of chemical pesticides, against two target proteins in insect, using molecular docking technique. Via MOE software, the best-scored position for every molecule was the only one achieved after the free binding energy (kcal/mol) was calculated. According to the results, the active molecules of conventional insecticides recorded the best results of binding interaction with the two examined target proteins (acetylcholinesterase and ecdysone receptor), followed by the molecule γ-eudesmol. The overall results indicated that among the tested compounds, the sesquiterpene γ-eudesmol was found to have the highest docking score with acetylcholinesterase and ecdysone receptors through the in silico study. Therefore, testing this ingredient on insects in both lab and field settings is strongly advised.